Evaluation of the supply chain to improve competitiveness and productivity in the metalworking industry in Barranquilla, Colombia (2018)
This paper studies the levels of competitiveness and productivity of the Metalworking Sector of the city of Barranquilla, based on the design of an evaluation model for the supply chain of companies belonging to that sector. The model consists of five critical aspects: supply, storage, inventory management, distribution and transport, and reverse logistics. These factors include a set of variables that evaluate the planning, execution, measurement, and control of supply chain management. The model was validated in five companies of the Metalworking Sector of the city of Barranquilla. Solutions for integral logistics practices were established in the procurement processes, taking into account quality standards of processes and security of the supply chain. It is concluded that the sector has presented a great economic growth in the country and it is necessary the optimization and continuous improvement of the productive processes through the monitoring and control of appropriate indicators